Pemanfaatan Pekarangan Rumah sebagai Ketahanan Pangan Keluarga pada Kelompok Wanita Tani - Rahman, Rahman; Hafizhah Al-Amanah; Eka Sudartik (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Food is the most important need in human life as a human resource for survival, but the increase in population causes the need for food to become greater which can result in a food crisis due to the narrowing of agricultural land.Continuous land function experts can threaten food security for a country by decreasing the amount of agricultural production due to the narrowing of agricultural land.Continuous land conversion can threaten food security for a country by decreasing the amount of agricultural production due to the narrowing of agricultural land.Home gardens can be a solution in maintaining food security by farming so that they can achieve food independence and become added value to the family's economy.Community service activities were carried out in Bonto Karaeng Village, located in Sinoa District, Bantaeng Regency, which has potential in the agricultural sector, targeting groups of women farmers as participants in community service activities carried out in September and October.The approach method is Participatory Rural Appraisal (PRA) with activities such as counseling to provide understanding and explain the flow of activities to be carried out.Training is providing knowledge and skills to participants by providing material and practice directly so that it is easy to understand. The mentoring method is used to provide solutions to problems and stimulate participants during activities. So this activity has a very positive impact so that it can produce food and additional sources of income for the community but still requires support from the parties involved.